Comparison of robotic-assisted laparoscopic hysterectomy to total laparoscopic hysterectomy in terms of operational complications at a regional institution: A retrospective study - Wataru Isono; Daiki Hiratsuka; Akira Tsuchiya; Akihisa Fujimoto; Osamu Nishii (Elsevier, 2023)
Objective: With the increased use of total laparoscopic hysterectomy (TLH), the use of robotic-assisted laparoscopic hysterectomy (RALH) has increased due to its technical advantages. On the other hand, RALH has some disadvantages, including its high cost, which includes not only the purchase price of robotic technology systems but also the running cost and long preparation time for setting assistant robots. Therefore, an overall understanding of the characteristics of RALH is needed. Study design: We reviewed the medical records of 432 patients with TLH and 93 patients with RALH from January 1, 2015, to December 31, 2022. In this analysis, we excluded certain cases with concomitant laparoscopic cystectomy (LC) and a heavy uterus (> 400 g). First, the patient characteristics of the TLH and RALH groups, including operation time and blood loss amount, were compared. Then, among these cases, we sought to predict difficult cases for TLH and RALH by identifying risk factors related to each of the following three categories of operational complications: "long operation time", "massive blood loss" and "other complications". For this purpose, multivariate logistic regression analyses were performed to assess the influence of each of 7 representative factors, namely, "advanced age", "high body mass index (BMI)", "nulliparity", "concomitant pelvic lymphadenectomy (PLA)", "heavy uterus", "abdominal adhesion", and "large leiomyoma". Results: In the simple comparison without various factors, there was an advantage of RALH in both the average operation time and blood loss amount. However, in the multivariate logistic regression analyses, a significant risk was detected in the following relationships: 1) between "long-term operation" and "abdominal adhesion" and 2) between "other complications" and "heavy uterus". Conclusions: RALH has sufficient advantages over TLH regarding at least in terms of blood loss amount; however, since RALH may have potential weaknesses in the context of complex cases, additional cases and analyses are needed.